If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 100 + 0.66(Y + -200) + 250 + 200 + 150 Reorder the terms: Y = 100 + 0.66(-200 + Y) + 250 + 200 + 150 Y = 100 + (-200 * 0.66 + Y * 0.66) + 250 + 200 + 150 Y = 100 + (-132 + 0.66Y) + 250 + 200 + 150 Reorder the terms: Y = 100 + -132 + 250 + 200 + 150 + 0.66Y Combine like terms: 100 + -132 = -32 Y = -32 + 250 + 200 + 150 + 0.66Y Combine like terms: -32 + 250 = 218 Y = 218 + 200 + 150 + 0.66Y Combine like terms: 218 + 200 = 418 Y = 418 + 150 + 0.66Y Combine like terms: 418 + 150 = 568 Y = 568 + 0.66Y Solving Y = 568 + 0.66Y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-0.66Y' to each side of the equation. Y + -0.66Y = 568 + 0.66Y + -0.66Y Combine like terms: Y + -0.66Y = 0.34Y 0.34Y = 568 + 0.66Y + -0.66Y Combine like terms: 0.66Y + -0.66Y = 0.00 0.34Y = 568 + 0.00 0.34Y = 568 Divide each side by '0.34'. Y = 1670.588235 Simplifying Y = 1670.588235
| 3x+47=6x+15 | | Y=100+0.6(Y-200)+250+200+150 | | Y=400+0.5(Y-200)+250+200+150 | | Y=100+0.5(Y-200)+250+200+150 | | 7+ln(27x)=22-2ln(x) | | y(y-6)-6(y-6)= | | 5(x-2)-3(x-1)=0 | | a(a-4)-4(a-4)= | | c(c-5)-5(c-5)= | | m(m-2)-2(m-2)= | | p=(a+b)*2 | | t(t+4)+4(t+4)= | | y(y+2)+2(y+2)= | | Y=150+0.7(Y-200)+50+0.2+200 | | b(b+7)-7(b+7)= | | r(r+4)-4(r+4)= | | p(p-2)+4(p-2)= | | x-4540=40 | | Y=150+0.7(Y-200)+50+0.2Y+200 | | x(x+2)+3(x+2)= | | -7(x-3)=63 | | 342+x=442 | | 8(2+z)-5(3-2z)= | | 2-3x=5x-2(x+8) | | 3(4-5a)-2(5-4a)= | | x-240=10 | | 4(y-6)-5(3y-1)= | | 7-2(x-4.5)=6-4x | | 6(3a+5)-3(2a-5)= | | 14+x=25 | | 2x+4y-7=0 | | 11(t+1)+2(t+5)= |